Prior consumption of a fat meal in healthy adults modulates the brain’s response to fat - Eldeghaidy, Sally; Marciani, Luca; Hort, Joanne; Hollowood, Tracey Ann; Singh, Gulzar; Bush, Debbie; Foster, Tim; Taylor, Andrew J.; Busch, Johanneke; Spiller, Robin C.; Gowland, Penny A.; Francis, Susan T. (American Society for Nutrition, 2016)
Background: Consumption of fat is regulated by reward and homeostatic pathways, but no studies have examined the role of the intake of a high fat meal (HFM) on subsequent brain activation to oral stimuli. Objective: We evaluated how prior consumption of a HFM or water load (WL) modulates reward, homeostatic and taste brain responses to subsequent delivery of oral fat. Methods: A randomized 2-way crossover design (1-week apart) was used to compare prior consumption of a 250mL HFM (520kcal) (rapeseed oil (440kcal), emulsifier, sucrose, flavor cocktail) or non-caloric WL on brain activation to the delivery of repeated trials of an oral flavored no-fat control stimulus (CS) or flavored fat stimulus (FS) in 17 healthy adults (11 male, age=25±2 years, BMI=22.4±0.8kg/m2). Analyses tested differences in brain activation to the CS and FS, and baseline cerebral blood flow (CBF), following the HFM and WL. Individual’s plasma cholecystokinin (CCK) concentration following the HFM was correlated with their BOLD activation. Results: Prior consumption of the HFM compared to the WL led to decreased anterior insula taste activation in response to both the CS (36.3%,P<0.05) and FS (26.5%,P<0.05). The HFM caused reduced amygdala activation (25.1%,P<0.01) in response to the FS compared to the CS (fat-related satiety). Baseline CBF significantly reduced in taste (insula (5.7%,P<0.01)), homeostatic (hypothalamus (9.2%,P<0.01), thalamus (5.1%,P<0.05))), and reward areas (striatum (9.2%,P<0.01)) following the HFM. Individual’s plasma CCK concentration negatively correlated with brain activation in taste, oral somatosensory and reward areas. Conclusions: To reduce obesity, policy in industry is to lower the fat content of foods. Our results in healthy adults show that a HFM suppresses BOLD activation in taste and reward areas compared to a WL. This understanding will help inform the reformulation of reduced-fat foods that mimic the brain’s response to high fat counterparts, and guide future interventions to reduce obesity.